1993
DOI: 10.1113/jphysiol.1993.sp019683
|View full text |Cite
|
Sign up to set email alerts
|

Cell volume regulation in rat thymocytes.

Abstract: SUMMARY1. DIOA (dihydroindenyl-oxy-alkanoic acid), a potent inhibitor of the K+-Cl-cotransport system, fully blocked regulatory volume decrease (RVD) in swelled rat thymocytes, with an IC50 of 2-2 + 0 5 x 10-5 mol 1-1 (mean + S.D., n = 4). Conversely, RVD was resistant to quinine, quinidine, apamin, cetiedil, amiloride, bumetanide and DIDS (4,4'-diisothiocyanostilbene-2,2'-disulphonate).2. DIOA-sensitive RVD followed mono-exponential kinetics, with th (half-lifetime) of 1-3 min and maximal capacity (Cmax) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 15 publications
0
31
1
Order By: Relevance
“…This is also true for crypt epithelia, as we have found that inhibition of either Clconductances with DIDS or tamoxifen (Fig. 4 B and C (25,26). When the CFTR -/-crypts were exposed to a hypotonic solution containing 1 ,uM valinomycin the RVD was restored (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…This is also true for crypt epithelia, as we have found that inhibition of either Clconductances with DIDS or tamoxifen (Fig. 4 B and C (25,26). When the CFTR -/-crypts were exposed to a hypotonic solution containing 1 ,uM valinomycin the RVD was restored (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…However, previous studies showed that at higher concentrations, i.e., 100 M, this drug can also partially inhibit Cl Ϫ and K ϩ channels (1,3,4). More specifically, a study showed that 100 M DIOA was able to reduce a swelling-activated Cl Ϫ conductance in human osteoblasts (4).…”
Section: Discussionmentioning
confidence: 99%
“…AINI is the initial, instantaneous Tc increase expected at to for a perfect osmometric behavior. Although, the RVD might have a more complicated time course, we used this curve fitting procedure to characterize the rate of the volume regulatory processes (Arrazola, Rota, Hannaert, Soler, and Garay, 1993). Tc crgL is cell height in isoosmotic conditions before the reduction of'trb.…”
Section: Protocols For Tc Measurementsmentioning
confidence: 99%